ANALISIS SWOT TANTANGAN DAN PELUANG NAHDATUL ULAMA DALAM MENJAGA KEUTUHAN NKRI - furqon wahyudi; Muhamad Marzuqkoni (STIT Sunan Giri Bima, 2021)
This study aims to identify and analyze strategies to answer nu challenges and opportunities in maintaining the integrity of the Republic of Indonesia by using SWOT analysis consisting of Strengths, Weaknesses, Opportunities and Threats as a strategy to increase the capacity of NU in maintaining the integrity of the Nkri This scientific paper is descriptive writing by reading nu social conditions in maintaining the integrity of the Republic of Indonesia using SWOT Analysis. To get accurate data, the method used is interview (in-depth interview), and look at the current social condition of the Republic of Indonesia. Several strategy steps will be selected using SWOT Analysis. The results of this scientific paper writing in which NU in answering challenges and opportunities in maintaining the integrity of the Republic of Indonesia has strengths, weaknesses, oppurnities, and threats in maintaining the integrity of the Republic of Indonesia. Swot analysis results that NU is able to maintain the integrity of the Republic of Indonesia by developing a movement of scientific studies, through online-based dkwa media, and so forth. As well as NU must exist or NU must be directly involved in addressing if there is information spread but the information is hoax